Can regulatory frameworks guarantee inclusive basic education? Insights from the physical environment in two types of basic schools in Cape Coast, Ghana (Journal of Science and Technology, 2022)
The passage of the needed regulatory frameworks in Ghana raised hopes that the physical envi-ronment in educational institutions would be improved to meet the spatial needs ofpupils with impairments. A spatial audit was conducted to evaluate the physical conditions in seven officially designated inclusive basic schools and seven mainstream basic schools where such pupils were enrolled in the Cape Coast Municipality of Ghana. The audit assessed the levels of compliance with the recommended universal design principles. Furthermore, questionnaires were adminis-tered to all the 41 pupils with restricted mobility enrolled in both school settings to explore their experiences with respect to physical access and space utilization. In-depth interviews were car-ried out with other purposively selected stakeholders including headteachers and teachers to further explore the emerging issues. Contrary to expectations the results revealed many danger-ous obstructions, unsuitable toilet facilities and overcrowded and poorly surfaced classrooms. These conditions obstructed the movements of the respondents and constrained their rights to education. The conclusion is that there is the need for collaboration among the stakeholders in the Municipality to go beyond the regulations to ensure the retrofitting of the school environ-ments, the improvement of basic school facilities like toilets and classrooms to enhance physical access and learning outcomes of the pupils.